2011
DOI: 10.1002/mnfr.201100535
|View full text |Cite
|
Sign up to set email alerts
|

Role of dietary proteins and peptides in cardiovascular disease

Abstract: Cardiovascular disease (CVD) is the leading cause of death for both men and women in the United States and most other countries. Therefore, a disease of such wide-ranging impact calls for the development of multiple viable strategies for prevention. Diet plays an important role in the development of the major risk factors of CVD such as low-grade systemic inflammation, hypertension, obesity, diabetes and atherosclerosis, the most significant. Thus, diet-based methods of prevention would not only be more feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 114 publications
(114 reference statements)
1
37
0
5
Order By: Relevance
“…Whey protein contains several proteins to which antiinflammatory properties are attributed (e.g. lactoferrin, β-lactoglobulin, and α-lactalbumin) in vitro and in animal studies [20,32,33]. Furthermore, a recent meta-analysis found that a whey supplement of 20 g/day or more significantly lowered CRP in human adults [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whey protein contains several proteins to which antiinflammatory properties are attributed (e.g. lactoferrin, β-lactoglobulin, and α-lactalbumin) in vitro and in animal studies [20,32,33]. Furthermore, a recent meta-analysis found that a whey supplement of 20 g/day or more significantly lowered CRP in human adults [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, this has yet to be investigated [20,21]. Interestingly, it is observed that an enteral nutrition formula containing whey protein resulted in a lower IL-6 level in ischemic stroke patients when compared with a formula containing casein [22].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the result needs to be repeated in a larger studies [20,32,33]. Furthermore, a recent meta-analysis found that a whey supplement 335 of 20 g/day or more significantly lowered CRP in human adults [34].…”
mentioning
confidence: 99%
“…However, this has yet to be investigated [20,21]. Interestingly, it is 60 observed that an enteral nutrition formula containing whey protein resulted in a lower IL-61 6 level in ischemic stroke patients when compared with a formula containing casein [22].…”
mentioning
confidence: 99%
“…Several health benefits have been attributed to these hydrolysates: e.g., blood pressure-lowering and cholesterol-lowering abilities, antimicrobial actions, antithrombotic effects and the enhancement of mineral absorption, cyto-or immuno-modulatory effects, and opioid activities (Agyei & Danquah, 2012;Cam & de Mejia, 2012;Korhonen, 2009;Lopez Exposito & Recio, 2006;Gauthier, Pouliot, & Saint-Sauveur, 2006;Mikkelsen, Rasmussen, Olsen, Barkholt, & Frokiaer, 2006;Pan et al, 2006;Mercier, Gauthier, & Fliss, 2004;Clemente, 2000;Hartmann & Meisel, 2007). Another important use of bioactive peptides is in support of the specific clinical needs of patients with phenylketonuria, acute and chronic liver disease, Crohn´s disease, pancreatiCopyright ©2013 ISEKI-Food Association (IFA) 10.7455/ijfs/2.1.2013.a4 tis and ulcerative colitis (Almeida & Souto, 2007;Clemente, 2000).…”
Section: Introductionmentioning
confidence: 99%